Smart Port as a Key to the Future Development of Modern Ports - Adrianna Karas (TransNav: International Journal on Marine Navigation and Safety of Sea Transportation, 2020)
Technological innovations gives the opportunity to create so-called Smart Ports. However, determining which technologies to choose, how to implement them remains a challenge. The research problem presented in the article is: Is the constant introduction and implementation of the concept of intelligent ports an irreversible trend determining the direction of development of modern seaports? The aim of the article is also to analyze projects introduced in the ports of the North Sea and Baltic Sea which are successively implementing the concept of a Smart Port. The article uses the method of analysis - mainly current analysis and prospective analysis.